2006
DOI: 10.1111/j.1365-2958.2006.05436.x
|View full text |Cite
|
Sign up to set email alerts
|

An α‐(1,4)‐amylase is essential for α‐(1,3)‐glucan production and virulence in Histoplasma capsulatum

Abstract: SummaryHistoplasma capsulatum is a dimorphic fungus that causes respiratory and systemic disease and is capable of surviving and replicating within macrophages. The virulence of Histoplasma has been linked to cell wall a-(1,3)-glucan; however, the role of this polysaccharide during infection, its organization within the cell wall, and its synthesis and regulation remain poorly understood. To identify genes involved in the biosynthesis of a-(1,3)-glucan, we employed a forward genetics strategy to isolate physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 110 publications
(141 citation statements)
references
References 66 publications
2
138
0
1
Order By: Relevance
“…On the basis of these data, the authors proposed a model which suggests that a small molecule consisting of a-(1,4)-linked glucose residues acts as a primer for the formation of longer, a-(1,3)-linked polymers by a-glucan synthases. As proposed by Marion et al (2006), the function of Amy1p, AmyD and related proteins could be to produce such a primer molecule. In this study, we have shown that AmyD indeed produces small maltooligosaccharides, with a preference for maltotriose, in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the basis of these data, the authors proposed a model which suggests that a small molecule consisting of a-(1,4)-linked glucose residues acts as a primer for the formation of longer, a-(1,3)-linked polymers by a-glucan synthases. As proposed by Marion et al (2006), the function of Amy1p, AmyD and related proteins could be to produce such a primer molecule. In this study, we have shown that AmyD indeed produces small maltooligosaccharides, with a preference for maltotriose, in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Although the enzymic activity of this protein has not been studied, a clear link was made with the production of cell wall aglucan, as a functional knockout was completely incapable of producing a-(1,3)-glucan (Marion et al, 2006). This hypothesis regarding the function of fungal GH13_5 aamylases is strengthened by the genomic organization of the encoding genes, many of which are arranged in a small cluster of genes also encoding an a-glucan synthase and a GPI-anchored a-glucanotransferase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations